Monitored anesthesia care (MAC) sedation: clinical utility of fospropofol - Eric A Harris; David A Lubarsky; Keith A Candiotti (Dove Medical Press, 2009)
Eric A Harris, David A Lubarsky, Keith A CandiottiDepartment of Anesthesiology, Perioperative Management, and Pain Medicine, University of Miami/Miller School of MedicineAbstract: Fospropofol, a phosphorylated prodrug version of the popular induction agent propofol, is hydrolyzed in vivo to release active propofol, formaldehyde, and phosphate. Pharmacodynamic studies show fospropofol provides clinically useful sedation and EEG/bispectral index suppression while causing significantly less respiratory depression than propofol. Pain at the injection site, a common complaint with propofol, was not reported with fospropofol; the major patient complaint was transitory perianal itching during the drug’s administration. Although many clinicians believe fospropofol can safely be given by a registered nurse, the FDA mandated that fospropofol, like propofol, must be used only in the presence of a trained anesthesia provider.Keywords: fospropofol, propofol, monitored anesthesia care